The Influence of Business Capital and Social Environment on Interest in Entrepreneurship (Case Study in the SPP PAPM GROUP, Asam Jujuhan District) - Alex Ferdinal; Dini Elida Putri; Mayroza Wiska; Yesi Gusteti; Andri Sonata Efendi (Greenation Research & Yayasan Global Resarch National, 2023)
PAPM Rural is a program to accelerate poverty alleviation in an integrated and sustainable manner. Problems experienced by small businesses such as the availability of capital for business development, and the social environment. The purpose of this study was to analyze the effect of business capital and the social environment on the interest in entrepreneurship in the SPP PAPM group, Asam Jujuhan District. The data collection method uses a Likert scale questionnaire. Methods of data analysis using quantitative methods with a population and a sample of 290 members of the SPP PAPM Asam Jujuhan group, analysis of research data using multiple linear analysis, t test, f test and the coefficient of determination with SPSS 20 data processing. The results of the research partially venture capital and social environment have a significant effect on interest in entrepreneurship. The f test shows that business capital and the social environment simultaneously have a significant effect on the interest in entrepreneurship. PAPM is advised to have training programs and online groups for members of the PAPM SPP group, in order to encourage the creation of an interest in entrepreneurship.